Instrumentos didácticos para fortalecer la vida y obra de Abraham Calazacón - Muñoz Cruz, Ricardo Santiago (2022)
This research stems from the need to explain the decline of ancestral knowledge regarding the life and work of Abraham Calazacón in the province of Santo Domingo in high school students. The main objective was to develop a proposal for a didactic instrument to strengthen the knowledge of the life and work of Abraham Calazacón in high school students in the province mentioned above. This work is descriptive and qualitative; the type of sampling was non-probabilistic for convenience; instruments such as virtual surveys were applied to students, and interviews with teachers of the Santo Domingo institutions, with a virtual didactic tool were carried out with the purpose of public knowledge. The interpretation and analysis of the results of the study instruments were carried out, concluding that it is necessary to use didactic tools since it is an ideal process to address the knowledge being lost and helps to understand and maintain history. Another point of this research is to give teachers an option to generate dynamics in their classes, seeing what didactic instruments can be used with their students. They are also participatory in their respective classrooms, leaving aside the emitter and receiver scheme, giving way to a modern education what has already been saying is examined, questioned, compared, refuted, and this provides teachers greater freedom to include more topics outside the curricular Maya and explore forgotten facts in Ecuador and cultures that have been disappearing, influenced by modernization, capitalism, and Eurocentric knowledge.